Adjuvant Cannabinoid Receptor Type 2 Agonist Modulates the Polarization of Microglia Towards a Non-Inflammatory Phenotype in Experimental Pneumococcal Meningitis - Pan, Steven D.; Grandgirard, Denis; Leib, Stephen L. (Frontiers in Cellular and Infection Microbiology, 2020)
Background: Microglia initiates and sustains the inflammatory reaction that drives the pathogenesis of pneumococcal meningitis. The expression of the G-protein cannabinoid receptor type 2 (CB2) in the brain is low, but is upregulated in glial cells during infection. Its activation down-regulates pro-inflammatory processes, driving microglia towards an anti-inflammatory phenotype. CB2 agonists are therefore therapeutic candidates in inflammatory conditions like pneumococcal meningitis. We evaluated the effects of JWH-133, a specific CB2 agonist on microglia cells, inflammation and damage driven by S.pneumoniae in vitro and in experimental pneumococcal meningitis. Materials/methods: Primary mixed glial cultures were stimulated with live or heat-inactivated S.pneumoniae, or lipopolysaccharide, and treated with JWH-133 or vehicle. Nitric oxide and cytokines levels were measured in the supernatant. In vivo, pneumococcal meningitis was induced by intracisternal injection of live S.pneumoniae in 11 days old Wistar rats. Animals were treated with antibiotics (Ceftriaxone, 100 mg/kg, s.c. bid) and JWH-133 (1 mg/kg, i.p. daily) or vehicle (10% Ethanol in saline, 100 µl/25g body weight) at 18 h after infection. Brains were harvested at 24 and 42 h post infection (hpi) for histological assessment of hippocampal apoptosis and cortical damage, and determination of cyto/chemokines in tissue homogenates. Microglia was characterization using Iba-1 immunostaining. Inflammation in brain homogenates was determined using membrane-based antibody arrays. Results: In vitro, nitric oxide and cytokines levels were significantly lowered by JWH-133 treatment. In vivo, clinical parameters were not affected by the treatment. JWH-133 significantly lowered microglia activation assessed by quantification of cell process length and endpoints per microglia. Animals treated with JWH-133 demonstrated significantly lower parenchymal levels of chemokines (CINC-1, CINC-2/ , MIP-3α), TIMP-1 and IL-6 at 24 hpi, and CINC-1, MIP-1α and IL-1α at 42 hpi. Quantitative analysis of brain damage did not reveal an effect of JWH-133. Conclusions: JWH-133 attenuates microglia activation and downregulates the concentrations of pro-inflammatory mediators in pneumococcal infection in vitro and in vivo. However, we didn't observe a reduction in cortical or hippocampal injury. This data provides evidence that inhibition of microglia by adjuvant CB2 agonists therapy effectively downmodulates neuroinflammation but does not reduce brain damage in experimental pneumococcal meningitis